Charles Sanders Peirce's semiotic analysis of human values in the film sound of freedom - Palinoan, Frans Fandy; Suma, I Made Markus; Tandiangga, Patrio; Dama, Arwin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research focuses on semiotic analysis of the film Sound of Freedom. This semiotic analysis aims to determine the interpretation and meaning related to the life values of the film. In this research the author uses elements from Charles Sanders Peirce's semiotic analysis method, with the limit of semiotic studies to the semantic level. This research is based on the understanding that film is not only a work of art that aims to entertain but can also be a communication medium that indirectly conveys human values. This film is an adaptation of a true story that tells the story of a United States government agent, Timothy Ballard (Jim Caviezel), who uncovers a child trafficking network in Colombia. The research method used by researchers is a qualitative research method using data originating from the results of document analysis and observations of texts. Technical data analysis was carried out using Charles Sander Peirce's semiotic theory. Researchers took Peirce's formula regarding objects which are classified into three, in the form of icons, indexes and symbols which are applied to each scene of the film Sound of Freedom. The results of this research show the human values contained in the film Sound of Freedom semantically. The results of this research show that the film Sound of Freedom contains human values. These human values include Respect for Human Dignity, solidarity, and sucriface for humanity.